Remembering Childhood Play (LEARNing Landscapes, 2019)
In looking back to childhood, and what constituted daily life, a case is made for unique ways of knowing that unfold through play, place, and tradition. A closer look at the relationship between childhood memory and the particularities of place, suggests that adult creativity, a sense of psychological stability, and an attitude of wonder even experimentation, are vital outgrowth. The loss of play from the realm of the child is considered a contributing factor to the current trauma epidemic within our society. How might returning to imagination, the body, free play, and the ecology of relationships renew the ways we live and make meaning in addition to the ways we heal and become more whole?
Keywords: imagination; body; play; nature; trauma; responsibility; reciprocity; relationships; reverence; wonder; creativity; ecstasy